Electrically Driven Reversible Phase Changes in Layered In2Se3 Crystalline Film. Issue 42 (4th October 2017) - Choi, Min Sup; Cheong, Byung‐ki; Ra, Chang Ho; Lee, Suyoun; Bae, Jee‐Hwan; Lee, Sungwoo; Lee, Gun‐Do; Yang, Cheol‐Woong; Hone, James; Yoo, Won Jong
Abstract: An unconventional phase‐change memory (PCM) made of In2 Se3, which utilizes reversible phase changes between a low‐resistance crystalline β phase and a high‐resistance crystalline γ phase is reported for the first time. Using a PCM with a layered crystalline film exfoliated from In2 Se3 crystals on a graphene bottom electrode, it is shown that SET/RESET programmed states form via the formation/annihilation of periodic van der Waals' (vdW) gaps (i.e., virtual vacancy layers) in the stack of atomic layers and the concurrent reconfiguration of In and Se atoms across the layers. From density functional theory calculations, β and γ phases, characterized by octahedral bonding with vdW gaps and tetrahedral bonding without vdW gaps, respectively, are shown to have energy bandgap value of 0.78 and 1.86 eV, consistent with a metal‐to‐insulator transition accompanying the β‐to‐γ phase change. The monolithic In2 Se3 layered film reported here provides a novel means to achieving a PCM based on melting‐free, low‐entropy phase changes in contrast with the GeTe–Sb2 Te3 superlattice film adopted in interfacial phase‐change memory. Abstract : Reversible crystalline–crystalline phase‐change memories are developed by stacking In2 Se3 on the bottom graphene electrode. This shows SET and RESET programmed states via formation and annihilation of periodic van der Waals' gaps. The reversible transition of monolithic In2 Se3 layered film demonstrates the potential of melting‐free and low‐entropy phase‐change memories.